Quantifizierung operationeller Risiken: Der Loss Distribution Approach - Peter Albrecht; Edmund Schwake; Peter Winter (German Risk and Insurance Review (GRIR), 2007)
Im Rahmen der aktuellen Diskussion über die effektive Messung operationeller Risiken auf der Basis interner Modelle hat vor allem der Loss Distribution Approach in der Literatur besondere Beachtung gefunden. Dieser Ansatz hat seine Wurzeln in einem traditionellen Ansatz der Versicherungsmathematik, der kollektiven Risikotheorie. Die vorliegende Ausarbeitung stellt daher die kollektive Risikotheorie in ihren Grundelementen dar, stellt die Verbindung zur Modellierung operationeller Risiken her und gibt einen Überblick über aktuelle Entwicklungen im Rahmen des Loss Distribution Approach. – – Given the current discussion on an effective measurement of operational risks on the basis of internal models, the Loss Distribution Approach has obtained special attention in the literature. This approach has its roots in a traditional field of insurance mathematics, the collective theory of risks. The present contribution presents the basic elements of collective risk theory, establishes the connection to the modelling of operational risks and gives an overview on recent developments of the Loss Distribution Approach.
Keywords: 360; kollektive Risikotheorie; operationelle Risiken; loss distribution approach; collective theory of risk; operational risk; loss distribution approach